Differential pacing from two sites to diagnose risk of ventricular arrhythmia and death. Issue 2 (18th December 2018) - Nayyar, Sachin; Kuklik, Pawel; Tomlinson, George; Suszko, Adrian; Chauhan, Vijay S.
Abstract: Background: QRS abnormalities may not be apparent in sinus rhythm in electrically stable cardiomyopathy patients who can have quiescent but highly arrhythmogenic substrate. Here, we test the hypothesis that differential changes in QRS construction during right‐ventricular apex pacing (RVP) as opposed to atrial pacing (AP) will identify latent substrate for ventricular arrhythmias (VA) and death. Methods: Forty patients with cardiomyopathy free of VA underwent baseline 114‐electrode body‐surface electrocardiogram during AP (100 beats per minute [bpm]) and RVP (100 and 120 bpm). The filtered‐averaged QRS at each electrode was deconstructed into individual intra‐QRS and post‐QRS ventricular myopotentials (VMP ). The primary outcome was VA or death. Prognostic accuracy of VMP was validated using V1 to V6 leads in another prospective cohort of 44‐cardiomyopathy patients. Results: Twenty‐six patients were eligible for initial analysis. After 5 ± 2 years of follow‐up, eight (31%) patients had VA (VAPos ) while rest were uneventful (VANeg ). During AP100, VAPos patients expressed more VMP than VANeg patients (16 ± 1 vs 12 ± 1, P  = 0.02). RVP100 and RVP120 in VAPos patients introduced an additional 5.5 ± 0.5 and 6.0 ± 0.5 VMP ( P  < 0.0001 vs AP100 ). The relative change with RVP120 versus AP100 in VANeg patients exceeded VAPos patients by 1.2 ± 0.5 VMP ( P  = 0.03). Increment in VMP count of <8 in lead‐V5 with RVP120 compared to AP100 best predicted VA (area under curve 0.81, P  = 0.01). In the validation cohort, primary outcome occurred in 13 (33%) patients. Native QRS features and AP100 alone failed to predict primary outcome. Patients with increment in VMP count of <8 in lead‐V5 with RVP120 versus AP100 had 7.9‐fold increased risk of primary outcome (95% confidence interval 1.01, 61.61; P  = 0.049). Conclusion: Cardiomyopathy patients at risk of VA or death perturb the QRS less than low‐risk patients with differential pacing. This functional response may be useful to identify arrhythmogenic substrate.